UPAYA JARINGAN NGO INTERNATIONAL POPS ELIMINATION NETWORK (IPEN) DALAM RENCANA AKSI PENGHAPUSAN PENGGUNAAN MERKURI DI INDONESIA PADA SEKTOR PERTAMBANGAN EMAS RAKYAT DAN KESEHATAN - Sumarlan "; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This Research is analyzes about the efforts of NGO network International POPs Elimination Network (IPEN) in action to resolve the complexity of exposure to mercury in artisanal small gold mining (ASGM) and health sector in Indonesia. Mercury is a well-known toxic that is damage for environment and acute health-effects. Mercury widely used and extent in artisanal gold mining due to the increase of ASGM sites and lack of explicit law. Environmental and health impatcs report not spread out, nevertheless case of health disorder and environment imbalance are exists in every mining site.In this research uses Tranznational Advocacy Network concept, which IPEN network have connectivity with NGOs worldwide. By applying Communication theory and level analysis is International Organization. These concepts aim to qualitatives method and library research for references.Some of IPEN network efforts are by conducting strategic approaches programme and mercury monitoring programme in three level; upstream, middle-stream, and down-stream, through the medium of NGO Balifokus Indonesia (IPEN Participating organization). These efforts create approximately of significant results such as legal-binding national laws (force by laws, ministrylaws, standard/SNI) and international (convention and ratification) to resolve of rampant mercury uses in Indonesia.Keywords: mercury, efforts, IPEN network, strategic approache, monitoring.